Potensi SIRIPLUS sebagai Balutan Luka Biodegradabel Berbasis Pati Singkong dan Ekstrak Sirih Merah (Piper crocatum): Systematic Literature Review - Mangde Anata Sindhu (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Chronic wounds, particularly diabetic ulcers, remain a major global medical challenge due to their high recurrence rate and substantial treatment costs. Current biomedical research increasingly focuses on wound dressings that are biodegradable, biocompatible, and therapeutically active. This article evaluates the potential of SIRIPLUS, an innovative wound dressing that integrates cassava starch (Manihot esculenta) as a natural polymer matrix and red betel leaf extract (Piper crocatum) as an active pharmacological agent. Using a systematic literature review approach referring to the PRISMA framework, the analysis synthesizes evidence on antioxidant and antibacterial activities, mechanical characteristics, and biodegradation performance. The reviewed studies indicate that Piper crocatum contains key secondary metabolites such as flavonoids, alkaloids, and tannins that may regulate p53, E-cadherin, and SOD1 pathways to support re-epithelialization and collagen deposition. Cassava starch offers film-forming ability, biocompatibility, and environmental degradability, while its physical performance can be optimized through plasticizers and cross-linking strategies. Overall, SIRIPLUS shows strong theoretical potential as an effective and environmentally sustainable modern wound dressing